The transformative potential of generative artificial intelligence - Vukmirović, Dragan; Kresović, Dejana (Napredak, 2024)
This paper analyses the transformative potential of generative artificial intelligence at macro, meso, and micro levels of social and economic structures. The aim is to determine the impact of these technologies on various aspects of society and economy, including business operations and the labour market. The potential of new technologies to increase productivity, transform business models, and create new professional roles has been examined through a comprehensive analysis of data and studies. It has been concluded that generative artificial intelligence can fundamentally change the labour market, globally increase gross domestic product, and improve both the public and private sectors. The paper provides insights into future trends and regulatory and structural changes that are necessary for optimising the application of generative AI.